"Naturfolk" i teori og praksis: Skildringen av samene og den nordlige kulturen i Knud Rasmussens Lapland" - Brøgger, Fredrik (Nordlit, 2014)
This article focuses on the portrayal of reindeer Sami in the Danish explorer Knud Rasmussen's early book Lapland from 1907, a work that has received relatively little attention in Rasmussen scholarship. His characterizations of the Sami reflect conventional, paternalistic ideas of race and culture at the turn of the century as well as romantic-sentimental conceptions of indigenous peoples as noble savages. Rasmussen is a lively storyteller, however, and the immediacy and vividness of his depictions simultaneously open up for perspectives that, at least partly, serve to undermine traditional stereotypes. If read closely, Rasmussen's narrative evinces clear tensions between its conventional generalizations about the reindeer Sami as an indigenous people and the direct, phenomenological descriptions that are the products of Rasmussen's actual encounter with them. At the same time his instinctive sympathy for the Sami is enlarged by his own, deeply personal yearning for a life style and culture grounded in Northern cold and winter, which he encountered growing up in Greenland and which runs like a leitmotif through all his writing.